รูปแบบการปรับพฤติกรรมการใช้ยารักษาตามแผนการรักษาของผู้สูงอายุความดันโลหิตสูงในชุมชน - ถนอมสัตย์, กมลภู; ตาปะสี, วิไล (Area Based Development Research Journal, 2015)
บทคัดย่อไม่สมบูรณ์ The study of Drug Compliance Behaviors Model of elders with hypertension in community This research and development aimed to investigate factors related to drug compliance behaviors and the effects of the drug compliance behaviors modification model among elderly with hypertension. The study consisted of 4 steps; step 1 was a study of factors related to the drug compliance behaviors of elderly with hypertension in community. A purposive sampling method was used to recruit 228 elderly patients. Content validity and language usage of this research were performed by three experts. Cronbach’s alpha coefficient was used to estimate the internal consistency reliability of the instrument and there found that the Cronbach’s alpha of each item was high ( =.81-.85). Step 2 was an assessment of the potentiality and social capital of the community. The Rapid Ethnography Community Assessment Program (RECAP) was used to collect the data. Step 3 was a Model presenting which aimed to promote drug compliance behaviors of elderly with hypertension. The data were collected from February to March, 2013. Descriptive statistic and content analysis were employed to analyze the data set. Step 4 was an examination of the effect Model on drug compliance behaviors according to the treatment practical guideline for elderly with hypertension. The participants were 65 older people who received drugs as treatment for hypertension. The study has taken place during June – September, 2013. Data were analyzed by Paired t-test and content analysis. The study found that the level of elderly-perceived barriers to use of medications, perceived family support, and perceived public health staffs support in the drug compliance were moderate ( = 2.88, 2.93, 3.24, SD. = 0.68, 0.43, 0.46, respectively). Sample subjects had a moderate level of drug compliance behaviors ( = 3.15, SD. = 0.70) and each of 3 dimensions which included drug keeping correctly, appropriate dosage, and observation of side effects of drug were inappropriate level ( = 2.31, 2.50, 2.53, SD. = 0.89, 0.84, 0.90, respectively). After that, a model for promoting the drug compliance behaviors was developed based on Clinical Practice Guideline (CPG) of hypertension. The model included 1) disseminate the warning alarm clock , 2) use of innovative aids such as a key chain pill box or necklace pill box to prevent the forgetting to take a drug and drug guideline in elderly with hypertension, and 3) arrange a drug use behavior modification program. The result of drug compliance behaviors model of elders with hypertension in community shown as the mean level of drug compliance behaviors of elderly with hypertension in the overall after participating was higher than before participating at a statistically significant level. 01 (t = 1.78, p-value <.01). The average score in each component which after participating is higher than before participating at a statistically significant level. 01, that consisted of right patient, appropriate dosage, and drug keeping correctly (t = 0.92, 1.35, 3.54, respectively, p-value <.01).